THE RIGHT TO FREEDOM OF EXPRESSION AND THE CRIMINAL LAW − THE JOURNEY THUS FAR - Shannon Hoctor (Obiter, 2022)
This article seeks to set out the application of the right to freedom of expression in the particular context of criminal law, taking into account developments in other Southern African jurisdictions where appropriate. In particular, the article examines the application of the right in the context of contempt of court, sexual morality, and pornography. Possible future applications of the right are also identified. Ultimately the article affirms the primary importance of the right to freedom of expression, and argues that the right should be zealously protected.